Contextual Effect of Community Health Service on the Use of Triple Elimination Service - Verasita, Prissy; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Triple elimination is the elimination of transmission of HIV, syphilis, and hepatitis B from mother to child. The Prevention of Mother to Child Transmission (PMTCT) program is a comprehensive activity. The basic condition of the case is carried out because of the importance of health promotion and early detection in strategies for managing HIV, Syphilis, and Hepatitis B infections. This study aimed to analyzecontextual effect of community health service on the use of triple elimination service in pregnant women. Subjects and Method: This was a cross sectional study conducted at 25 community health centers in Sragen Regency, Central Java, from June to July 2019. A sample of 200 pregnant women was selected by stratified random sampling. The dependent variable was the use of triple elimi